Peran Pendidikan Agama Islam Bagi Perempuan dalam Proses Mendidik Anak - Rohmat Mulyana Sapdi (UIN Sunan Gunung Djati Bandung, 2023)
One of the boldest change that has happened in the Jahiliyah dan Islamiyah is the shifting values of the women. At first, women hold no values in the society and Islam changed it into the opposite. Aside from women contribution in the Islamic heritage after that. The true role of a women is to be a mother that educate their children in an Islamic way. Understanding Islam is important for a women due to Islam has changed their values in the society and then their well-understood of Islam will affect their children like how Islam did to them. By using a normative approach, namely literature research, it can be concluded that mothers have an important role in training children to understand religion in order to prepare children for the future world. The rules of Islam from the past are absolute based on the Qur'an and Hadith have not changed since then. When women correctly understand the Islamic parenting, then the purpose of Islamic education contained in Surat At-Tahrim (66) verse 6 and Surat Luqman (31) verses 12-19